2019
DOI: 10.2147/ndt.s210199
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nicotine consumption during the prodromal phase of schizophrenia – a review of the literature</p>

Abstract: Recent research has fueled a debate concerning the role of nicotine in the emergence of schizophrenia. The three main hypotheses are: (a) the self-medication effect, (b) the causal relationship hypothesis, or (c) the shared diathesis hypothesis. To explore this role, the study of nicotine consumption during the initial prodromal phase of schizophrenia offers important opportunities. In the present work, 10 relevant studies are reviewed, out of 727 retrieved citations, in order to address questions regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 87 publications
(153 reference statements)
0
13
0
Order By: Relevance
“…However, with both SMI and chronic physical health conditions, a prodromal stage or period of undiagnosed disease may occur and therefore diagnosis dates may not give a clear indication of temporal association. Furthermore, previous studies have found increased physical health problems prior to schizophrenia(57, 58) and bipolar disorder diagnoses(59) and that health risk factors for physical health conditions such as smoking(60) and alcohol and drug misuse may be present prior to SMI diagnosis(61).…”
Section: Discussionmentioning
confidence: 98%
“…However, with both SMI and chronic physical health conditions, a prodromal stage or period of undiagnosed disease may occur and therefore diagnosis dates may not give a clear indication of temporal association. Furthermore, previous studies have found increased physical health problems prior to schizophrenia(57, 58) and bipolar disorder diagnoses(59) and that health risk factors for physical health conditions such as smoking(60) and alcohol and drug misuse may be present prior to SMI diagnosis(61).…”
Section: Discussionmentioning
confidence: 98%
“…The association between tobacco smoking and SCHZ has gained attention in recent years [ 108 ]. However, scant studies in prodrome patients and in animal models of SCHZ investigated this comorbidity during adolescence, which has the potential to identify mechanisms of nicotine interference in the development of SCHZ.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy nicotine dependence is prevalent in 16–46% of those in the prodromal phase of schizophrenia (Gogos et al, 2019 ), leading researchers to question if there is a causal relationship between schizophrenia and smoking (i.e., does smoking increase the risk for schizophrenia, or does having schizophrenia promote smoking habits to alleviate disease symptoms? ), if the risk for smoking and schizophrenia share common mechanistic underpinnings, or both (Khokhar et al, 2018 ).…”
Section: Tobacco and E-cigarettesmentioning
confidence: 99%